Basophil activation after nonsteroidal anti‐inflammatory drugs stimulation in patients with immediate hypersensitivity reactions to these drugs. Issue 5 (17th January 2014) - Ariza, Adriana; Fernandez, Tahia D.; Doña, Inmaculada; Aranda, Ana; Blanca‐Lopez, Natalia; Melendez, Lidia; Canto, Gabriela; Blanca, Miguel; Torres, Maria J.; Mayorga, Cristobalina
Abstract Nonsteroidal anti‐inflammatory drugs (NSAIDs) are the drugs most frequently involved in allergic reactions of which two main types exist: IgE‐mediated and crossintolerance. The diagnosis of crossintolerance reactions is often based on the drug provocation test. The potential value of the basophil activation test (BAT) was evaluated using different basophil markers in the diagnosis of patients with crossintolerance to NSAIDs and cutaneous symptoms. We studied 46 patients with crossintolerance to NSAIDs and 45 tolerant controls. BAT was performed with acetyl salicylic acid, paracetamol, diclofenac, dipyrone, naproxen, and ibuprofen at four different concentrations using CD193 and CD203c as basophil markers and CD63 as activation marker. We compared BAT results using CD193+ or CD193+CD203c+ for basophil selection and found a significant increase in the stimulation index when using CD193+CD203c+ in both patients and controls (P = 0.004 and P = 0.017, respectively). Selection of living cells only produced an increase in basophil stimulation in patients for both CD193+ and CD193+CD203c+ (P < 0.001 for both), whereas in controls there was no change with CD193+ and a decrease with CD193+CD203c+ (P = 0.001). We found that CD193+CD203c+ increased the percentage of positive cases in patients and controls when compared with CD193+. When excluding dead cells, there was an increase of 21.7% in patients and 10% in controls. These results indicate that using CD193+CD203+, excluding dead cells, is the best approach for BAT although this test is not recommended for the diagnosis of patients with crossintolerance to NSAIDs owing to its low sensitivity and specificity. © 2014 International Society for Advancement of Cytometry